Analisis Keputusan Mahasiswa Dalam Menentukan Kopi Berdasarkan Kandungannya - Firda Nasywaa Sabila; Hafshah Zainab Mujahidah Ibnatu Muslim; Irfan Setiawan; Nazhwa Praditha Budiman (International Forum of Researchers and Lecturers, 2024)
As students who tend to be oriented towards in-depth knowledge and understanding, analysis is key in making decisions regarding coffee consumption. In this case, coffee content analysis is the main factor taken into consideration in determining their choice. The findings of this study indicate that students consider various factors in their decisions in choosing the type of coffee based on its ingredients. Influencing factors include caffeine, antioxidants, fat, and sugar content. College students have different preferences regarding the level of caffeine in coffee, which can be influenced by their energy needs and their tolerance level for caffeine. The aim of this research is to analyze the factors that are the main considerations for students in determining the choice of coffee based on its content. This research uses a qualitative and quantitative approach that focuses on questionnaires with a 1-4 Likert scale and bold interviews. The number of participants in this research was 53 people and was reduced to 6 people being interviewed. This qualitative and quantitative approach shows that analysis of factors in selecting coffee based on its content is not a benchmark for coffee consumption. The coffee consumed by several respondents is adjusted to their body condition or personal health. The factors that become a benchmark for choosing coffee consumption are not based on its content but based on needs and health.